Genomically Silent Refractory Gastric Cancer in a Young Patient Exhibits Overexpression of CXCL5 - Jonathan Hernandez; Michael A. Turner; Prerna Bali; Mojgan Hosseini; Michael Bouvet; Kaitlyn Kelly; Marygorret Obonyo (Current Oncology, 2022)
Gastric cancer is the third leading cause of cancer-related deaths, with more than one million new cases and approximately 841,000 deaths annually worldwide. We report a case of a young patient (25 years old) with an aggressive form of gastric cancer. The patient had previously been treated for Helicobacter pylori (H. pylori), which is a main risk factor for developing gastric cancer. Genetic testing showed an E-cadherin (CDH1) germline mutation of unknown significance. After eight cycles of chemotherapy, a positron emission tomography (PET) scan showed disease progression with an enlarging hypermetabolic right adnexal mass suspicious for metastatic disease. Tumor pathology demonstrated invasive and poorly differentiated gastric carcinoma. The analysis of the tumor biopsy indicated the very high expression of a chemokine, C-X-C motif chemokine 5 (CXCL5). The combination of H. pylori infection with an existence of a rare CDH1 mutation could have contributed to this aggressive gastric cancer.